Analysis of the Influence of the Marketing Mix on Consumer Purchasing Decisions Using the Structural Equation Modeling Method - Kuliman Kuliman; Sri Kemala; Diah Permata; Almasdi Almasdi; Nurul Huda Aina Fitri (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2023)
This study aims to determine the effect of the 7P marketing mix, namely product, price, location, promotion, people, physical evidence, and process on Budiman Swalayan Jembes’s consumers that affect their decision-making when purchasing at Budiman Swalayan Jembes. This study uses the Structural Equation Modeling (SEM) method with the Smart PLS version 3.0 program. The data used in this study are data obtained from respondents totaling 155 people through filling out questionnaires. Data analysis conducted in this study is an evaluation of the measurement model (outer model), evaluation of the structural model (inner model) and hypothesis testing. The results of this study indicate that of the seven variables studied, three of them influence consumer purchasing decisions. The three variables that influence consumer purchasing decisions of Budiman Swalayan Jembes are product variables, price variables and location variables. As for the other four variables, namely the promotion variable, the people variable, the physical evidence variable and the process variable, the analysis shows that there is no influence on consumer purchasing decisions at Budiman Swalayan Jembes.